2019
DOI: 10.1177/1557988319832749
|View full text |Cite
|
Sign up to set email alerts
|

Masculine/Instrumental and Feminine/Expressive Traits and Health, Well-Being, and Psychological Distress in Spanish Men

Abstract: Many studies have explored the relationship between masculine norms and men’s health outcomes. There are few recent studies published on the relationship between masculine/instrumental and feminine/expressive traits and men’s health and well-being. The current cross-sectional study examines whether masculine/instrumental and feminine/expressive traits are associated to men’s health and well-being. Participants were 1,870 Spanish men, aged 21 to 64 years. Results from hierarchical multiple regression analysis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
(76 reference statements)
3
10
0
2
Order By: Relevance
“…The results provided converge and support the literature that states that openness to positive traits of the opposite gender role is an essential trait for successful ageing [66]. Moreover, the research conducted with the general population has found that people whose self-concept includes both instrumental and expressive characteristics report greater self-rated health and well-being [19,22,23,71]. These results could be important for the design of interventions with the elderly, which should include strategies for women to develop characteristics such as independence, self-confidence, individuality, and assertiveness; and for men to develop empathy, sensitivity to the needs of others, or warmth.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results provided converge and support the literature that states that openness to positive traits of the opposite gender role is an essential trait for successful ageing [66]. Moreover, the research conducted with the general population has found that people whose self-concept includes both instrumental and expressive characteristics report greater self-rated health and well-being [19,22,23,71]. These results could be important for the design of interventions with the elderly, which should include strategies for women to develop characteristics such as independence, self-confidence, individuality, and assertiveness; and for men to develop empathy, sensitivity to the needs of others, or warmth.…”
Section: Discussionsupporting
confidence: 81%
“…Although masculine norms vary by place and time [18], research on conformity to masculine norms has reported that individuals’ conformity to masculine norms is related with a range of negative psychological outcomes and reduced help seeking, although the results may vary depending on the specific dimension of the masculine norm [16]. The masculine/instrumental trait has been found to be more associated with the well-being of men and women than the feminine/expressive trait [19,20,21,22,23]; however, it has also been found that femininity is associated with optimal mental functioning [22,23,24]. It has been suggested that the strict adherence to masculine and feminine roles can limit the range of potential behaviours and choices of women and men [25], which would entail a limitation to the development of those personal characteristics which do not conform to what society considers appropriate to each gender.…”
Section: Introductionmentioning
confidence: 99%
“…Self-esteem ended up being an important predictor of psychological distress for the male sample and the only predictor for the females. These results coincide with those of other studies [ 33 , 38 ] and confirm the importance of self-esteem on psychological well-being for both men and women. These results force us to consider the value of self-esteem and psychological well-being as health contributors, as highlighted by some authors in studies on psychological distress and the workplace [ 32 , 33 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…These results coincide with those of other studies [ 33 , 38 ] and confirm the importance of self-esteem on psychological well-being for both men and women. These results force us to consider the value of self-esteem and psychological well-being as health contributors, as highlighted by some authors in studies on psychological distress and the workplace [ 32 , 33 , 34 , 35 ]. The results highlight the lack of importance of social support in predicting psychological distress, as it was only statistically significant in the male group, despite literature reporting social support as a protective factor of psychological distress.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation